High-energy gamma radiation from extragalactic radio sources. - Dermer, C. D.; Schlickeiser, R.; Mastichiadis, A. (1992)
We propose that the important relationship between 3C 273 and 3C 279, the first two extragalactic sources detected at > 100 MeV energies, is their superluminal nature. In support of this conjecture, we propose a kinematic focusing mechanism, based on Compton scattering of accretion-disk photons by relativistic nonthermal electrons in the jet, that preferentially emits gamma rays in the superluminal direction.
Keywords: Accretion Disks; Compton Effect; Computational Astrophysics; Distribution Functions; Extragalactic Radio Sources; Gamma Ray Astronomy; Gamma Ray Observatory; Radio Emission; Relativistic Electron Beams; Space Radiation; Spaceborne Astronomy